1 Penggunaan Bahan Tambahan Pangan Pada Pengolahan Makanan Industri Rumah Tangga Di Kecamatan Payakumbuh Barat Kota Payakumbuh - Fadhilla, F.; Faridah, Anni; Gusnita, Wiwik (Journal of Home Economics and Tourism, 2017)
This study aimed to describe the use of food additives in the food processing industry in the District of West Payakumbuh, Pespecially for dyes, flavorings, sweeteners and preservatives. This research uses a qualitative approach by using a descriptive method with data collection techniques of observation, interviews and documentation. Then for checking the validity of the data, the researchers did the test of credibility by doing the renewal observations, increased persistence, tringulasi with peers and negative case analysis. The results of the research showed that the entrepreneur using both natural and synthetic food additives. Synthetic food additives types which used are yellow, red and green synthetic dyes, flavoring MSG, and sakarine artificial sweeteners. Processed products of home industry are sanjai balado merah, hijau, karak kaliang, lento, roda gandiang, sanjai lidi, and ganepo. The amount and dosage used are not based on the regulation of Ministry of Health Republic of IndonesiaKeyword: Food Additives, Home Industry, District of West Payakumbuh, Food Processing